(untitled) (Research, Society and Development, 2020)
The present study sought to verify the correlation between hospitalization rates for mental and behavioral disorders in adolescents and coverage by CAPS, ESF and bed distribution in the state of Paraná. This is an ecological study, from 2008 to 2015. For the correlation calculations, the Spearman coefficient was used with a level of significance of 5%. There was progress in the coverage of CAPS and FHS across the state, and a reduction in hospital beds. Strong correlation between CAPS coverage and psychiatric hospitalization only in the regions of Pato Branco (r = 0.99; p <0.001) and Londrina (r = 0.73; p = 0.038), in the others there was no statistical significance. The regional offices of Ponta Grossa (r = -0.76; p = 0.028) and Irati showed a strong correlation (r = -0.70; p = 0.021) between the rates of hospitalization and FHS coverage, respectively. Only the regional area of ​​União da Vitória showed a strong correlation between treatment beds and hospitalization rate (r = 0.7; p = 0030). Advances in CAPS and FHS coverage were identified across the State, however, there were no great results in reducing hospitalizations for mental and behavioral disorders among adolescents in Paraná.